Microstructure and properties of Cr18-Ni8 steel joints brazed with BNi7+3%Cu composite solder. (February 2018) - Li, Guojin; Zhang, Peilei; Shi, Haichuan; Yu, Zhishui
Abstract: A vacuum brazing process using BNi7+3% Cu composite solders to braze Cr18-Ni8 steel was carried out. The joint can be divided into three zones: Isothermally Solidified Zone (ISZ), Athermally Solidified Zone (ASZ) and Diffusion Affected Zone (DAZ). The characteristics of microstructure were observed by scanning electron microscope (SEM). The element distribution in the Cr18-Ni8 steel brazed joint and the content of elements in the organizations were measured by energy dispersive spectrum (EDS). The brazed joints are mainly composed of FeNi3 phases, Ni solid solutions, Ni3P eutectic structures and Cr-Ni-P compounds. The effects of different factors on the microstructure and properties were studied. The growth rate of solid solution increased first and then decreased with the rise of temperature. The hardness of diffusion zone increased first and then decreased when the brazing temperature went up. Cu played an important role to increase the hardness of brazing seam. Prolonging holding time or reducing the brazing gap width was beneficial for the formation of the solid solution. The hardness increased with the extension of holding time. The brazing gap had little effect on hardness. The fracture mode of the joint was ductile fracture. The joints had higher strength when the brazing temperature increased. Highlights: BNi7+3%Cu was chosen to braze Cr18-Ni8 steel. The joints are mainly composed of FeNi3 phases, Ni solid solutions and Ni3P, Cr-Ni-P compounds. The effects of different parameters on the microstructure and properties were analyzed. Cu played an important role on the properties of the joints. The fracture form of the brazed joint is the brittle fracture. Raising temperature can effectively improve the strength of the joint.